THEORETICAL ANALYSIS OF SOCIAL PROTECTION OF CIVIL SERVANTS IN THE UZBEKISTAN - Khojiev Zavkiddin Farkhodovich (Journals Park Publishing, 2024)
In this paper we make an attempt to examine the theoretical aspects of social protection and guarantees for civil servants. In particular, we focus on the importance of social protection and guarantees for civil servants, as well as political, legal, socio-economic and spiritual measures established by law, in the productivity of their activities. Moreover, we try to methodically and methodologically cover social protection and material support systems for civil servants, and group the parameters of the attractiveness of social protection. We also analyze the approaches to meet the material and spiritual needs of a person within the framework of social protection.
Keywords: social state, civil service, social protection, guarantee, social security, social insurance, social assistance, organizational and legal support, motivation, incentives.